Courage In Philip Noyce's Salt Movie (2010): A Feminist Approach - Huda , Khoerul (2012)
The problem of the study is to reveal how major character reflects her courage. The objective of the study is to analyze the film based on the structural analysis and based on the feminist approach. The research is qualitative research. Type of the data of the study is text and image from two data sources: Primary and secondary. The Primary data source is Salt movie by Philip Noyce released in 2010. While the secondary data sources are other materials taken from books, journals and internet related to the study. Both data are collected through library research and analyzes by descriptive analysis. The study comes to the following conclusion. First, based on the structural analysis of each element, it shows that the character and characterization, casting, plot, setting point of view, theme, mise-en-scene, cinematography, sound, and editing are related one another and form of unity. Second, based on the feminist analysis the writer concludes that the problems faced by the major character cause her become courageous woman.